Pengaruh beban kerja perawat terhadap kinerja perawat Di ruang rawat inap rumah sakit (Systematic Literature Review): The effect of nurse workload on nurse performance in hospital inpatient rooms (Systematic Literature Review) - Desy Nur Hidayah; Tomy Suganda (UPPM STIKES Pemkab Jombang, 2026)
The workload of nurses is one of the important factors that affect the quality of health services in hospitals, especially in inpatient units with 24-hour service demands. This study aims to analyze the influence of nurse workload on nurse performance through a systematic literature review approach. The method used refers to the PRISMA (2020) guidelines, with data sources from Google Scholar, PubMed, Garuda, and ScienceDirect in the range of 2019–2025. Out of a total of 1,230 articles identified, 12 studies met the inclusion criteria for further analysis. The results showed a significant negative influence between workload and nurse performance. Some studies show insignificant results, where workload does not directly affect performance. These findings indicate that the relationship between workload and performance is complex, influenced by other factors such as burnout, work stress, motivation, and organizational support. Professional adaptation mechanisms, work experience, solid teamwork, and supportive leadership have been proven to moderate the impact of workload on nurse performance. Workload is not always a direct determinant, but acts as a trigger variable that affects psychological and organizational factors. This research emphasizes the importance of proportional workload management and organizational system support to improve nurse performance and health service quality.